The correlation of physical development and results of the training process of young gymnasts - Vlasyuk, A. O.; Bevza, T. V.; Bedareva, A. A.; Bakaev V. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the influence of compensatory exercises on the harmony of physical development and the efficiency of the body parts of young gymnasts as a single kinematic system.